Substitution between accrual and real earnings management: The role of independent commissioners and audit committee - Sri Hastuti; Doddy Setiawan; Ari Kuncara Widagdo (University of Merdeka Malang, 2020)
The aim of the research is to investigate a substitution between accrual-based earnings management and real activities manipulation based upon the independence of the board of commissioners and the audit committee (number of audit committee members and number of audit committee meetings). This study involved a sample of manufacturing firms in the period of 2009-2014 with 664 observations. The hypothesis testing using multiple regression tests was carried out to obtain some evidence that the independence of the board of directors has no significant effect on accrual-based earnings management but a significant negative effect on real activities manipulation, to the extent of gaining stronger impacts after 2012. The number of audit committee members has a significant positive effect on accrual-based earnings management and a significant negative effect on real activities manipulation through abnormal production costs without any differences between pre and post 2012. The number of audit committee meetings has a significant effect on accrual-based earnings management but does not significantly influence real activities manipulation. In addition, substitution from accrual-based earnings management to real activities manipulation occurred due to the existence of independence of the board of commissioners that comes with a stronger impact on the real activities manipulation after 2012. Furthermore, there was a substitution from accrual-based earnings management to real activities manipulation based on the number of audit committee members without any different effects before and after 2012.JEL classification: G34, M40, M41 How to Cite:Hastuti, S., Setiawan, D., Widagdo, A. K. (2020). Substitution between accrual and real earnings management: The role of independent commissioners and audit committee. Jurnal Keuangan dan Perbankan, 24(2), 225-240.DOI: https://doi.org/10.26905/jkdp.v24i2.4060